Understanding Religious Moderation and Hadith Towards Religious Tolerance Among Lecturers at UIN Sumatera Utara - Muhammad Idris; Muhammad Akbar Rosyidi Datmi (al-Afkar, Journal For Islamic Studies, 2025)
This study aims to examine the understanding of students of the State Islamic University of North Sumatra towards the concept of religious moderation and tolerance-themed hadiths, and to instill them in their attitudes in a pluralistic academic environment. Using a qualitative approach with a phenomenological design, data were collected through in-depth interviews, participant observation, and documentation. Informants were selected purposively from various scientific backgrounds relevant to the issue of Islam and interfaith tolerance. The results of the study indicate that most lecturers understand religious moderation within a normative framework, with an emphasis on the values ​​of tawasuth, tasamuh, adl, and musawah. Lecturers with a background in hadith science interpret hadith contextually and inclusively, especially in responding to the pluralistic social reality of Indonesia. In contrast, lecturers from non-hadith fields tend to use a literal approach or ignore the relevance of tolerance hadiths in teaching practices. In the context of academic life, most lecturers show an open attitude towards differences through active participation in interfaith activities. However, challenges are still faced in the form of sectarian bias, lack of lecturer training, and the influence of identity politics. This study recommends strengthening cross-disciplinary disciplines, integration of climate based on maqasid al-shariah and moderation, and institutional collaboration with figures and institutions of different faiths. This study provides an important contribution in the approach to developing living hadith and internalizing the value of religious moderation in Islamic higher education environments as an effort to build an inclusive and peaceful academic culture.